2016
DOI: 10.1039/c6dt02473d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of partial substitution of Ni by Mg on the structural, magnetic and spectroscopic properties of the double perovskite Sr2NiTeO6

Abstract: In this report, the structural, magnetic and spectroscopic properties of the freeze-drying synthesized Sr2Ni1-xMgxTeO6 (x = 0.0, 0.1, 0.2, 0.3 and 0.5) oxides are analyzed by means of X-ray powder diffraction (XRPD) and neutron powder diffraction (NPD), electron paramagnetic resonance, diffuse reflectance and magnetic susceptibility. The XRPD and NPD data analysis using the mode-crystallography approach have revealed that at room temperature (RT), all the compositions are monoclinically distorted with the spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…10 This limits Te 6+ participation in J2 exchange, where a d-orbital contribution from the B'' cation is required. We also highlighted that the d 10 /d 0 effect extends beyond simple cubic structures to a large range of 3d transition metal B' = Co 11,12 , Ni [13][14][15] and Cu [16][17][18][19] double perovskites, all of which follow the same principle based on the nonmagnetic B''-site: d 0strong J2 (type II) or d 10 -strong J1 (type I/Néel order).…”
Section: Cations and O 2p Orbitals (Ie B'-o-b''-o-b')mentioning
confidence: 77%
“…10 This limits Te 6+ participation in J2 exchange, where a d-orbital contribution from the B'' cation is required. We also highlighted that the d 10 /d 0 effect extends beyond simple cubic structures to a large range of 3d transition metal B' = Co 11,12 , Ni [13][14][15] and Cu [16][17][18][19] double perovskites, all of which follow the same principle based on the nonmagnetic B''-site: d 0strong J2 (type II) or d 10 -strong J1 (type I/Néel order).…”
Section: Cations and O 2p Orbitals (Ie B'-o-b''-o-b')mentioning
confidence: 77%
“…Typically, Fe 3+ , Ni 2+ , and Ni 0 have associated EPR signals, while Fe 2+ , Fe 0 , and Ni 3+ do not. [ 39–41 ] As displayed in Figure 2e, no obvious resonance signal was detected from NiSe 2 (black line). On the other hand, broad EPR signals were obtained for all the samples containing Fe, with the highest signal intensity being observed for the sample containing the lowest amount of Fe, Ni 0.75 Fe 0.25 Se 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The Rietveld renement revealed that all the compounds are in monoclinic unit cell in the I2/m space group, as reported by previous study. 16,17 The rened lattice angles for all compounds are a ¼ g ¼ 90 , whereas ß for x ¼ 0.0, 0.2, 0.4, 0.6, 0.8, 1.0 are 90.018, 90.063, 90.046, 90.111, 90.141 and 90.063 , respectively; the rened unit cell volumes (V) of each samples are 247.580, 248.241, 248.692, 250.580, 251.199 and 252.042Å 3 , respectively. These results show that the unit cell volume of the crystal structure increases as the doping increases from x ¼ 0.0 to x ¼ 1.0.…”
Section: Xrd Analysismentioning
confidence: 99%